PENGARUH MODEL PEMBELAJARAN POE TERHADAP KEMANDIRIAN DAN KEMAMPUAN BERPIKIR DIVERGEN PADA MATA KULIAH IPAS - Encep Iman Hadi Sunarya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research carried out aims to (1) determine the influence of the POE learning model on the learning independence of first semester students majoring in PGSD FKIP Sebelas April University, (2) determine the influence of the POE learning model on the divergent thinking ability of first semester students majoring in PGSD FKIP Sebelas April University, (3) determine the influence of the POE learning model on learning independence and on the divergent thinking ability of first semester students majoring in PGSD FKIP Sebelas April University. This research uses a quantitative approach to this type of research Quasi Experimental Design. The population is all first semester students majoring in PGSD FKIP Sebelas April University, sampling was carried out through Cluster Random Sampling. The sample was first semester students from class I-D (experimental class) and class I-E (control class). Data collection took the form of a learning independence questionnaire and divergent thinking ability tests in the basic science concepts course, as well as data analysis using the MANOVA test. The results of the research show that (1) the significance value is 0.000 < 0.05 so that H1 is accepted, so it is concluded that there is an influence of the POE learning model on the learning independence of first semester students majoring in PGSD FKIP Sebelas April University, (2) the significance value is 0.000 < 0.05 so H1 is accepted, so it is concluded that there is a significant influence of the POE learning model on the divergent thinking ability of first semester students majoring in PGSD FKIP Sebelas April University, (3) the significance value is 0.000 < 0.05 so H1 is accepted, then it is concluded that it exists. The significant influence of the POE learning model on learning independence and the divergent thinking ability of first semester students majoring in PGSD FKIP Sebelas April University.